A preliminary study on purification and characterization of lipase(s) produced by cryptococcus diffluens D44 - PİNAR, ORKUN (My University, 2023)
In the present work, preliminary purification, and characterization of lipases from Cryptococcus diffluens D44, which was isolated from petroleum sludge, were performed. In the purification steps, subsequential to acetone precipitation, lipases from C. diffluens D44 were purified by DEAE Sepharose resulting in two different peaks, named Lip1 and Lip4. Sephadex G-100 size-exclusion chromatography was also performed for further purification of Lip1 and Lip4 and resulted in three different lipases as Lip1-1 (1.0 purification fold with 2.4% recovery), Lip1-2 (0.8 purification fold with 7.2% recovery), and Lip4-1 (1.2 purification fold with 4.5% recovery). As a result of characterization studies of these three lipases resulting from different peaks, optimum temperatures were found as 60 °C, 65 °C, and 65 °C for Lip1-1, Lip1-2, and Lip4-1, respectively. Furthermore, thermal stability studies were conducted at 50 °C, 60 °C, and 70 °C, and lipases of C. diffluens D44 maintained over 70% of their initial activity at 50 °C. The optimum pH for Lip1-1 and Lip1-2 was pH 9.0 although pH 5.0 was for Lip4-1. Considering the organic solvent effect on lipase activity, 10% methanol enhanced the relative activity of Lip1-1 and Lip4-1 while 10% ethanol caused a decrease in the relative activity of lipases except for Lip1-2. According to the indicated features based on the results, these different lipases from C. diffluens D44 could be promising candidates for industrial and biotechnological applications. To the best of our knowledge, this is the first study on the purification of lipases from C. diffluens D44

Bu çalışmada, petrol çamurundan izole edilmiş olan Cryptococcus diffluens D44'ten lipazların saflaştırılması ve karakterizasyonuna ait ön çalışmalar gerçekleştirilmiştir. Saflaştırma çalışmalarında, aseton çöktürmesinin ardından, C. diffluens D44’ye ait lipazlar, DEAE Sepharose ile saflaştırılarak iki farklı tepe noktası elde edilmiş, Lip1 ve Lip4 olarak isimlendirilmiştir. Sephadex G-100 boyut ayırma kromatografisi kullanılarak, Lip1 ve Lip4'ün saflaştırılması sonucunda da, Lip1-1 (%2,4 geri kazanım ile 1,0 saflaştırma katında), Lip1-2 (%7,2 geri kazanım ile 0,8 saflaştırma katında) ve Lip4-1 (%4,5 geri kazanımla 1,2 saflaştırma katında) olmak üzere üç farklı lipaz elde edilmiştir. Farklı piklerden elde edilen bu üç lipazın karakterizasyon çalışmaları sonucunda, Lip1-1, Lip1-2 ve Lip4-1 için belirlenen optimum sıcaklıklar sırasıyla 60 °C, 65 °C ve 65 °C olarak bulunmuştur. Ayrıca, termal stabilite çalışmaları 50 °C, 60 °C ve 70 °C'de yürütülmüş, C. diffluens D44'ten elde edilen lipazlara ait enzim aktivitesi 50 ºC'de başlangıç aktivitesinin %70'inin üzerinde korunabilmiştir. Optimum pH değerlerine bakıldığında, bu değerler, Lip1-1 ve Lip1-2 için pH 9.0 olarak bulunurken, Lip4-1 için pH 5.0 olarak belirlenmiştir. Ayrıca organik çözücülerin lipaz aktivitesi üzerindeki etkileri dikkate alındığında %10 metanol, Lip1-1 ve Lip4-1'in nispi aktivitesini arttırırken, %10 etanol ise Lip1-2 dışındaki lipazların nispi aktivitesini azaltmıştır. Çalışmadaki belirlenen özelliklere göre, C. diffluens D44'ten elde edilen bu farklı lipazların, endüstriyel ve biyoteknolojik uygulamalar için umut verici adaylar olabileceği düşünülmüştür. Bildiğimiz kadarıyla bu çalışma, C. diffluens D44'ten lipazların saflaştırılmasına ilişkin ilk çalışma niteliğindedir
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Engineering, Computing & Technology (ENG); Lipase; Cryptococcus diffluens D44; purification; characterization; Lipaz; saflaştırma; karakterizasyon